Involvement of nuclear receptor corepressor 2 (NCOR2) in estrogen-induced repression of arcuate Kiss1 expression in female rats - Marina TAKIZAWA; Sae MIYAZAKI; Hitomi TSUCHIDA; Mayuko NAGAE; Shunsuke SEKI; Masumi HIRABAYASHI; Fumitaka OSAKADA; Naoko INOUE; Hiroko TSUKAMURA; Yoshihisa UENOYAMA (The Journal of Reproduction and Development)
Hypothalamic arcuate (ARC) kisspeptin neurons are considered the gonadotropin-releasing hormone pulse generator in rats. In virgin rats, the expression of the ARC kisspeptin gene (Kiss1) is repressed by proestrous levels of estradiol-17β (high E2) but not by diestrous levels of E2 (low E2). In lactating rats, ARC Kiss1 expression is repressed by low E2 during late lactation. This study aimed to investigate whether nuclear receptor corepressor 2 (NCOR2, encoded by Ncor2), an estrogen receptor α corepressor, is involved in the estrogen-induced repression of ARC Kiss1 expression in rats. Double in situ hybridization for Kiss1 and Ncor2 revealed that approximately 80% of ARC Kiss1-expressing cells co-expressed Ncor2 in ovariectomized (OVX) + low E2 virgin rats, while approximately 90% of ARC Kiss1-expressing cells co-expressed Ncor2 in OVX + low E2 lactating rats. To further examine the role of Ncor2, we studied the effects of Kiss1-dependent Ncor2 knockdown on ARC Kiss1 expression and luteinizing hormone (LH) pulses. An adeno-associated virus vector carrying Cre-activated short hairpin RNA (shRNA) for Ncor2 was administered to the ARC in two Kiss1-Cre rat models: OVX + high E2 Kiss1-Cre virgin rats and OVX + low E2 Kiss1-Cre lactating rats. Ncor2-shRNA treatment significantly increased the number of ARC Kiss1-expressing cells and the intensity of Kiss1 signals in OVX + high E2 virgin rats but failed to fully restore low E2-induced Kiss1 repression in lactating rats. The Ncor2-shRNA treatment failed to affect LH pulses in both models. These findings suggest that NCOR2 in ARC kisspeptin neurons mediates high E2-induced repression of ARC Kiss1 expression in virgin rats.